Letter from Robert S. Mulliken to Harrison Shull, 1960 - Mulliken, Robert Sanderson (1960)
Letter between Robert S. Mulliken and Harrison Shull, American quantum chemists, concerning upcoming speaking engagements by Mulliken.
Keywords: Shull, Harrison; Mulliken, Robert Sanderson; Chemists; Cornell University; Quantum chemistry; University of California, Berkeley; Nobel Prize winners; Physicists; Harvard University